2018
DOI: 10.5902/1984686x28819
|View full text |Cite
|
Sign up to set email alerts
|

Intervenção precoce: práticas e representações

Abstract: Com o objetivo de se conhecer as práticas dos profissionais de Intervenção Precoce (I.P.) e analisar em que medida essas práticas coincidem com as representações das famílias, realizou-se o presente estudo que contou com a participação de uma profissional de I.P. e a mãe de uma criança que beneficia dos serviços prestados por essa mesma profissional. Trata-se de um estudo qualitativo de cariz compreensivo e interpretativo. Foi utilizado como instrumento de colheita de dados a entrevista semiestruturada. Os pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 2 publications
0
5
0
1
Order By: Relevance
“…The results of the research showed the prevalence of consultations in adults (population between 20 and 59 years old), as the study that refers that, with the passage of age and worsening of diseases, the demand for speech therapy services grows (16) , it is important that Speech Therapy takes a close look at these age groups. On the other hand, the work with the child population was evident in the participants of the present study, which may be important to avoid further changes and worsening of orofacial myofunctional disorders (OMD) at later ages (17) .…”
Section: Discussionmentioning
confidence: 88%
“…The results of the research showed the prevalence of consultations in adults (population between 20 and 59 years old), as the study that refers that, with the passage of age and worsening of diseases, the demand for speech therapy services grows (16) , it is important that Speech Therapy takes a close look at these age groups. On the other hand, the work with the child population was evident in the participants of the present study, which may be important to avoid further changes and worsening of orofacial myofunctional disorders (OMD) at later ages (17) .…”
Section: Discussionmentioning
confidence: 88%
“…Thus, students´ characteristics need to be known, identifying their needs, and using precise strategies and resources to lead them to educational success. This success does not have to be the same for everyone (6,7) .…”
Section: Discussionmentioning
confidence: 99%
“…This different concept has limited the prevention and early identification of children who do not have immediate access to the services they need (1) . Given the high prevalence of children with LD in the educational context, it is pertinent to identify those with difficulties and at risk of evidencing language problems in their academic career, in the context of language performance as early as possible (7,24) . Dysnomy is one of LD that since the early 1970s has become of interest to researchers in the field of adult aphasia, learning disorders, speech and language disorders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations